PEMENUHAN KEBUTUHAN DASAR MANUSIA SETELAH MELAHIRKAN PADA FASE LETTING GO - Sarwoko; Sulastri (Jurnal Kebidanan, 2024)
After giving birth a woman needs good conditions and all needs are met both physically and psychologically, there are often further problems that we do not want if the physical and psychological needs are not met in women after giving birth. This study aims to find out the extent of physical and psychological needs of mothers after giving birth in the letting go phase in Wonorejo village, Kalijambe, Sragen. This study was conducted with a total sample, namely 45 mothers giving birth in the letting go phase, in the RW of Wonorejo village. The results of the study were obtained as follows, 26 (57.8%) mothers after giving birth accessed to Health Services as many as 26 (57.8%) said moderate, which means that when needed health workers are still in the category of enough to provide convenience when needed, while the knowledge of Postpartum Care of mothers after childbirth is still very low so that it requires the active role of pets.Keywords: After Childbirth, Basic, Physical And Psychological Needs